Ductile‐to‐brittle transition behavior of low molecular weight polycarbonate under carbon dioxide. Issue 5 (19th April 2017) - Taguchi, Tomoaki; Miike, Ramu; Hatakeyama, Tomoe; Saito, Hiromu
Abstract : We investigated the stress–strain behavior of low molecular weight polycarbonate for optical disc grade (OD‐PC) under carbon dioxide (CO2 ) at various pressures, and compared the results with that under ambient pressure at various temperatures. Elongation at break decreased sharply with increased CO2 pressure at around 2 MPa, while the elastic modulus decreased gradually up to 6 MPa. These results indicate that the tensile property changed from ductile to brittle with increased CO2 pressure, although the molecular motion is accelerated due to the plasticization effect of CO2 . Such ductile‐to‐brittle transition is similar to that observed under elevated temperatures caused by chain disentanglement due to accelerated molecular motion. Although the changes of tensile properties were similar, the craze structure obtained by the brittle behavior was different, i.e., a filamented‐craze structure was obtained under high‐pressure CO2, while a lace‐like one was obtained under elevated temperatures. POLYM. ENG. SCI., 2017. © 2017 Society of Plastics Engineers